Optimizing tournament performance: A reversal theory view of arousal and motivation in soccer - Geisler, G.; Kerr, J. H. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In comparison to regular season play, the demands of tournament-style competition are such that players must repeatedly "switch on and off," both physically and mentally, over relatively short periods of time. Against this backdrop, a reversal theory framework was used to assess dimensions of felt/preferred arousal (excitement, alertness, energy) and the motivational states (serious-playful, negativity-conformity, mastery-sympathy, self-others) of indoor soccer players at a one-day tournament in Canada. The aims were to address the correlations of these measures with game outcomes and players` self-ratings of performance, and to consider the implications for mental skills strategies in tournament formats. Methods The State of Mind Indicator for Athletes (SOMIFA; Kerr & Apter, 1999) was administered to 33 players, from four competing teams, after each of their three firstround matches. The SOMIFA required players to reflect on their performance quality and their arousal and motivational states in the games they had just played. Chisquare and logistic regression analyses were then performed to examine possible relationships between the variables. Results and Discussion In terms of game outcome, the analyses indicated that players were more likely to be on winning teams if they held a conformist motivational orientation during matches; that is, if they were inclined to follow the instructions of coaches and others closely, as opposed to a more individualistic motivational desire to do one`s own thing. In addition, winning was related to a preference for high levels of physical energy but lower preferred excitement. With respect to performance quality, more positive self-ratings were also associated with higher levels of preferred energy. These findings underline the distinction between mental and physical preparation and the importance of developing collective team objectives for optimal tournament play. Conclusions Coaches and mental trainers should teach players that their unique abilities and skills are best applied within the parameters of team interests and tactics. Moreover, players should be counseled on the effective combination of both arousing muscular activation and psychological relaxation strategies, respectively, to foster high physical energy alongside an equally important sense of mental calm.